Immunogenicity and safety of a 14-valent pneumococcal polysaccharide conjugate vaccine (PNEUBEVAX 14™) administered to 6–8 weeks old healthy Indian Infants: A single blind, randomized, active-controlled, Phase-III study - Matur, Ramesh V.; Thuluva, Subhash; Gunneri, Subbareddy; Yerroju, Vijay; reddy Mogulla, Rammohan; Thammireddy, Kamal; Paliwal, Piyush; Mahantshetty, Niranjana S.; Ravi, Mandyam Dhati; Prashanth, S.; Verma, Savita; Narayan, Jai Prakash (Vaccine, 2024)
Introduction of pneumococcal conjugate vaccines (PCVs) reduced the number of cases of pneumococcal disease (PD). However, there is an increase in clinical and economic burden of PD from serotypes that are not part of the existing pneumococcal vaccines, particularly impacting pediatric and elder population. In addition, the regions where the PCV is not available, the disease burden remains high. In this study, immunogenicity and safety of the BE’s 14-valent PCV (PNEUBEVAX 14™; BE-PCV-14) containing two additional epidemiologically important serotypes (22F and 33F) was evaluated in infants in comparison to licensed vaccine, Prevenar-13 (PCV-13). This is a pivotal phase-3 single blind randomized active-controlled study conducted at 12 sites across India in 6–8 weeks old healthy infants at 6–10–14 weeks dosing schedule to assess immunogenic non-inferiority and safety of a candidate BE-PCV-14. In total, 1290 infants were equally randomized to receive either BE-PCV-14 or PCV-13. Solicited local reactions and systemic events, adverse events (AEs), serious AEs (SAEs), and medically attended AEs (MAAEs) were recorded. Immunogenicity was assessed by measuring anti-PnCPS (anti-pneumococcal capsular polysaccharide) IgG concentration and functional antibody titers through opsonophagocytic activity (OPA), one month after completing three dose schedule. Cross protection to serotype 6A offered by serotype 6B was also assessed in this study. The safety profile of BE-PCV-14 was comparable to PCV-13 vaccine. Majority of reported AEs were mild in nature. No severe or serious AEs were reported in both the treatment groups. For the twelve common serotypes and for the additional serotypes (22F and 33F) in BE-PCV-14, NI criteria was demonstrated as defined by WHO TRS-977. Primary immunogenicity endpoint was met in terms of IgG immune responses for all 14 serotypesof BE-PCV-14. Moreover, a significant proportion of subjects (69%) seroconverted against serotype 6A, even though this antigen was not present in BE-PCV-14. This indicates that serotype 6B of BE-PCV-14 cross protects serotype 6A. BE-PCV-14 also elicited comparable serotype specific functional OPA immune responses to all the serotypes common to PCV-13. BE-PCV-14 was found to be safe and induced robust and functional serotype specific immune responses to all 14 serotypes. It also elicited cross protective immune response against serotype 6B.These findings suggest that BE-PCV-14 can be safely administered to infants and achieve protection against pneumococcal disease caused by serotypes covered in the vaccine. The study was prospectively registered with clinical trial registry of India – CTRI/2020/02/023129.